???????? ????? ??????? ?????? ?? ????? ????? ??????? ? ??????? ????? ????? ?????? ?? ??????? ???????? ????????? ???????? ?????? ????????“Cooperative Integrated Reading And Composition” ?????? ????? - Nida Nurun Nabila; Sholehan Sholehan (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2019)
The process of learning Arabic in MTS Negeri 1 Surabaya is still traditional. Especially in reading and writing skills. This causes students difficulty understanding the subject matter. The objectives of this study are: (1) To find out the reading and writing skills of Grade VIII students at MTs Negeri 1 Surabaya. (2) To find out the application of the Cooperative Integrated Reading and Composition "model using simple comic methods to improve their reading and writing skills. (3) To find out the effectiveness of the" Cooperative Integrated Reading And Composition "model with simple comic methods in improving their reading and writing skills The results of this study are: that the "Cooperative Integrated Reading and Composition" model with a simple comic method is effective in improving reading skills with a t-count = 13.9 and writing skills with a t-count = 14.7. Hypothesis results using the T-test symbol indicate that t count > ttable means that the null hypothesis (Ho) is returned and the hypothesis (Ha) can be accepted.